Perbandingan Ketahanan Pangan Komoditi Padi Indonesia dan Malaysia - Ramadhanty, Pinkan; Kasron, Norzalila; Siregar, Gustina; Manik, Juwita Rahmadani (UNIVERSITAS LABUHANBATU, 2024)
This research aims to find out how food security compares for rice commodities in Indonesia and Malaysia. This research was conducted in September 2023. The data used in this research is secondary data sourced from the Indonesian Central Bureau of Statistics (BPS) and the Malaysian Agricultural Office. The method used in this research is a qualitative method which is presented through sorting data and then comparing the data. The results of the research show that in terms of production factors, Indonesia is quite superior compared to Malaysia. The amount of rice production in Indonesia is quite significant compared to the amount of rice production in Malaysia each year. Keywords: food security, rice, Indonesia, Malaysia